A Special Family of Stacked Central Configurations: Lagrange Plus Euler in One - Cornelio, J. Lino; Álvarez-Ramírez, M.; Cors, Josep M. (Journal of dynamics and differential equations, 2019)
We show the existence of a family of stacked central configurations in the planar five-body problem with a special property. Three bodies m 1 , m 2 and m 3 , ordered from left to right, are collinear and form an Euler central configuration, and the other two bodies m 4 and m 5 , together with m 2 are at the vertices of an equilateral triangle and form a Lagrange central configuration.